The development and application of Laboratory Animal Science in China - Vergara, Patri; Morahan, Grant (Animal models and experimental medicine, 2018)
According to statistics, in the field of life science, animal experiments account for 60% and therefore make a significant contribution to research in the field. Animal experiments have also enabled the study of genetic engineering and the acquisition of desired genetic traits to produce new insights into the molecular bases of disease. [...]it can be seen that laboratory animals and animal experiments play an extremely important role in promoting the development of life science. [...]they believe that comparative medicine is an interdisciplinary subject of Laboratory Animal Science and Medicine, focusing on the similarities and differences in medical problems in humans and animals of different species.